Giant axonal neuropathy: A differential diagnosis of consideration - Edem, Pınar; Karakaya, Mert; Wirth, Brunhilde; Okur, Tuncay Derya; Yiş, Uluç (The Turkish Journal of Pediatrics, 2019)
Giant axonal neuropathy (GAN) is a rare neurodegenerative disorder affecting both the central and peripheral nervous systems progressively. The recessive mutations of the GAN gene are responsible for the disease. Although some clinical aspects, like coarse and kinky hair, are suggestive, other diseases may interfere with diagnosis. We describe a case who previously had been diagnosed with and treated for chronic inflammatory demyelinating polyradiculoneuropathy (CIDP); after re-evaluation, genetic testing was received, and the patient was diagnosed with GAN.
Keywords: giant axonal neuropathy; neurodegenerative diseases; polyneuropathies